2010
DOI: 10.1111/j.1365-3059.2010.02400.x
|View full text |Cite
|
Sign up to set email alerts
|

Potential biological control of clubroot on canola and crucifer vegetable crops

Abstract: Clubroot caused by Plasmodiophora brassicae is an emerging threat to canola (Brassica napus) production in western Canada, and a serious disease on crucifer vegetable crops in eastern Canada. In this study, seven biological control agents and two fungicides were evaluated as soil drenches or seed treatments for control of clubroot. Under growth cabinet conditions, a soil-drench application of formulated biocontrol agents Bacillus subtilis and Gliocladium catenulatum reduced clubroot severity by more than 80% r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
85
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 100 publications
(97 citation statements)
references
References 40 publications
1
85
0
1
Order By: Relevance
“…The low efficiency of the biofungicide in the biological control of the disease is not uncommon (Peng et al 2011) and is due to different factors, such as environmental and soil microflora conditions and pathogen spore density and viability, among others, as shown in the present study. The low efficiency of T. harzianum and positive effect of a cyazofamid-based product in the control of clubroot are reported by Peng et al (2011) in canola, although these authors also showed a promising effect of other antagonists such as Bacillus subtilis and Gliocladium catenulatum.…”
Section: Control Typementioning
confidence: 87%
See 2 more Smart Citations
“…The low efficiency of the biofungicide in the biological control of the disease is not uncommon (Peng et al 2011) and is due to different factors, such as environmental and soil microflora conditions and pathogen spore density and viability, among others, as shown in the present study. The low efficiency of T. harzianum and positive effect of a cyazofamid-based product in the control of clubroot are reported by Peng et al (2011) in canola, although these authors also showed a promising effect of other antagonists such as Bacillus subtilis and Gliocladium catenulatum.…”
Section: Control Typementioning
confidence: 87%
“…The biotrophic pathogen P. brassicae is a common soil protozoan (Niwa et al 2008, Peng et al 2011. It has a complex life cycle divided into two phases: in the soil, where it survives in the form of robust resting spores (Dixon 2009), and in plants, infecting the roots and causing cell hyperplasia and hypertrophy with the consequent formation of galls.…”
Section: Palavras-chavementioning
confidence: 99%
See 1 more Smart Citation
“…In another study examining the efficacy of seven biological control agents and two fungicides at reducing clubroot severity, two biological control agents. Bacillus subtilis Ehrenberg & Cohn and Gliocladium catenulatum Gilman & Abbott, were found to be as effective as the fungicides fluazinam and cyazofamid under greenhouse conditions (18). Unfortunately, these biological control agents were not effective under field conditions, perhaps due to the relatively dry weather experienced that year (18).…”
mentioning
confidence: 96%
“…No pesticides are registered for clubroot management on canola (Howard et al, 2010). In response, research is being carried out to examine factors that could be part of an integrated and sustainable disease management package for clubroot that includes biological control (Peng et al, 2010), the impact of seeding date (Gossen et al, 2009), soil amendments and bait crops (Ahmed et al, 2011). Optimum management may reduce the development and spread of new pathotypes that can overcome the clubroot-resistant commercial cultivars that have recently been developed, and so could contribute to reducing the threat that clubroot poses to the canola industry in western Canada.…”
Section: Introductionmentioning
confidence: 99%